Conservation: When extremes meet rarity. - Baizurah,SN; Groner,VP (Curr Biol, 2026)
A catastrophic five-day rain triggered over 50,000 landslides across the core habitat of the critically endangered Tapanuli orangutan in Sumatra, potentially killing a significant proportion of the population and raising urgent questions about rare species' viability in a changing climate.